English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4x+y=4
3x-y=3

2007-03-28 04:06:29 · 7 answers · asked by bratt1 1 in Science & Mathematics Mathematics

7 answers

these are called linear equations in two variables or simultaneous equations

4x+y=4 .........(1)
3x-y=3 .........(2)

add equations (1) and (2)

4x+y + 3x - y=4+3
=>7x=7
=>x=1

substitute x=1 in equation (1)
=>4(1)+y=4
=>4+y=4
=>y=4-4=0

so x=1 and y=0

2007-03-28 04:09:02 · answer #1 · answered by Daredevil 2 · 0 2

You can find the intersection point of these two lines by different methods, but the easiest one for this problem is called elimination. It means that you want to get rid of one of the variables by adding or subtracting the two equations.

Notice that in the top equation, you have a +y and in the bottom you have -y. Since these are opposite, if you add them together they will cancel each other out.

Add the two equations just like any other adding problem, by lining up the common terms, x's over x's, y's over y's, = over =. Then add striaght up and down.

4x+y=4
3x-y=3

7x = 7

Solve this equation for x by dividing both sides by 7, to "undo" the 7 times x on the left side. Then you will find that x = 1.

Now that you have one of the variables, simply substitute that value into one of the original equations.

4x + y = 4
4(1) + y = 4
4 + y = 4

Subtract 4 from each side to get rid of the 4 on the left.

4 + y = 4
-4 -4
y = 0

So your answers are x = 1 and y = 0. So the coordinates of the point where those 2 lines cross is (1,0).

2007-03-28 11:15:46 · answer #2 · answered by T F 4 · 0 0

4x + y = 4
3x - y = 3

I think the easiest way is eliminated them!

First, make the x or y coeficient same! in this problem, i same the y coeficient

4x + y = 4
3x - y = 3

then annihilate the y

4x+y = 4
3x-y = 3
-----------+ (in this prob, we use +, because 1y+(-1y)=0)
7x = 7
x = 1

then substitue the x into the linier system, up to you to use which system

4x+y=4
4(1)+y=4
4+y=4
y=0

or

3x-y=3
3(1)-y=3
3-y=3
y=0

And the solving is {x,y | x = 1, and y =0}

2007-03-28 11:16:02 · answer #3 · answered by Paige Matthews H 1 · 0 0

4x +3x +y -y = 4 +3

7x = 7

x = 1

4×1 +y = 4

4 +y = 4

y = 0

2007-03-28 11:09:12 · answer #4 · answered by math freak 3 · 0 0

4x + y = 4
3x - y = 3

Add the equations together and you get:

7x = 7
x = 1

Go back and substitute x in either equation:

4(1) + y = 4
y = 0

2007-03-28 11:15:19 · answer #5 · answered by JOhn M 5 · 0 0

First solve one of the equatons for y:
y=4-4x

Then substitute this value for y into the other equation:
3x-(4-4x)=3
3x-4+4x=3
7x=7
x=1

Then solve for y:
y=4-4x1
y=0

2007-03-28 11:13:01 · answer #6 · answered by Nick P 1 · 0 0

4x+y=4 -------(1)=> y=4-4x put this in (2)
3x-y=3 --------(2)

3x-4+4x=3 => 7x=7 => x=1 put this in (1) => y=0.

2007-03-28 11:20:09 · answer #7 · answered by sandy 2 · 0 0

fedest.com, questions and answers